Shortened tuberculosis treatment regimens: what is new? - Rossato Silva, Denise; Carvalho de Queiroz Mello, Fernanda; Battista Migliori, Giovanni (Jornal brasileiro de pneumologia, 2020)
Given the global burden of tuberculosis, shortened treatment regimens with existing or repurposed drugs are needed to contribute to tuberculosis control. The long duration of treatment of drug-susceptible tuberculosis (DS-TB) is associated with nonadherence and loss to follow up, and the treatment success rate of multidrug-resistant tuberculosis (MDR-TB) is low (approximately 50%) with longer regimens. In this review article, we report recent advances and ongoing clinical trials aimed at shortening regimens for DS-TB and MDR-TB. We discuss the role of high-dose rifampin, as well as that of clofazimine and linezolid in regimens for DS-TB. There are at least 5 ongoing clinical trials and 17 observational studies and clinical trials evaluating shorter regimens for DS-TB and MDR-TB, respectively. We also report the results of observational studies and clinical trials evaluating a standardized nine-month moxifloxacin-based regimen for MDR-TB. Further studies, especially randomized clinical trials, are needed to evaluate regimens including newer drugs, drugs proven to be or highly likely to be efficacious, and all-oral drugs in an effort to eliminate the need for injectable drugs.